Bombieri's Theorem in Short Intervals (Communications in Mathematical Research, 2021)
Under the assumption of sixth power large sieve mean-value of Dirichlet $L$-function, we improve Bombieri's theorem in short intervals by virtue of the largesieve method and Heath-Brown's identity.